Technologies and Stages of Creating Educational Resources Based on Artificial Intelligence - Muhiddinov Muhriddin Nuriddin oglu (Scientific Trends, 2025)
This article thoroughly explores technologies and stages involved in developing artificial intelligence (AI)-based educational resources in specialized schools. The study examines methods of employing AI and ICT to enhance the effectiveness of the pedagogical process. It provides an in-depth analysis of the capabilities of adaptive and individualized learning facilitated by artificial intelligence technologies, alongside pedagogical monitoring and interdisciplinary integration. Specific indicators and criteria have been developed to evaluate students' knowledge and determine their motivation.
Keywords: Artificial intelligence, ICT, educational resources, adaptive learning, pedagogical monitoring, interdisciplinary integration, pedagogical effectiveness, information security, individualized education.